Computational prediction of the spin-polarized semiconductor equiatomic quaternary Heusler compound MnVZrP as a spin-filter. Issue 43 (7th July 2020) - Hoat, D. M.; Hoang, Duc-Quang; Naseri, Mosayeb; Rivas-Silva, J. F.; Kartamyshev, A. I.; Cocoletzi, Gregorio H.
Abstract : Mechanism of d–d interactions and d-electron distributions in the equiatomic quaternary Heusler compound MnVZrP. Abstract : In this work, a new equiatomic quaternary Heusler (EQH) compound, MnVZrP, is predicted using first principles calculations. Simulations show the good stability of the material, suggesting experimental realization. Results show that MnVZrP is a magnetic semiconductor material, exhibiting semiconductor characteristics in both spin channels, however, with strong spin-polarization. Electronic band gaps of 0.97 and 0.47 eV are obtained in the spin-up and spin-dn states, respectively. Mainly the d–d coupling regulates the electronic band structure around the Fermi level. Strain effects on the electronic properties of the proposed compound are also investigated. Simulations give the total magnetic moment of 3 μ B satisfying the Slate-Pauling rule. The main magnetic contributions are given by the Mn and V constituents. The results presented here suggest the promising applicability of EQH MnVZrP as a spin-filter. Additionally, the elastic property calculations indicate the mechanical stability and elastic anisotropy. The work may be useful in the magnetic Heusler alloys field, introducing a new member to the small group of magnetic semiconductor EQH compounds for spin-filter applications.